Recovery of extracellular lipase from burkholderia sp. st8 in aqueous two-phase systems - Ooi, Chien Wei (2011)
Lipase has widespread applications in various industrial fields and high demand in enzyme market. However, conventional purification methods for lipase are tedious and require several rounds of purification steps. Therefore, development of a highly efficient and cost-effective protocol for the purification of lipase is essential. Aqueous two-phase system (ATPS) can be used as an attractive alternative for the purification of lipase from complex feedstock. Thus, this experimental investigation focused on the design of ATPS protocol as simplified and rapid purification technique for the microbial lipase of Burkholderia sp. ST8. Different approaches of ATPS were considered and each of the ATPS was evaluated independently. Polyethylene glycol (PEG) 6000/potassium phosphate ATPS was employed for the purification of Burkholderia sp. ST8 lipase from fermentation broth. The simplicity and effectiveness of PEG/phosphate ATPS for the purification of lipase were proven in this study. Optimum condition for the purification of lipase was obtained in PEG 6000/potassium phosphate ATPS with TLL of 42.2% (w/w), VR of 2.70, pH 7, addition of 1% (w/w) sodium chloride (NaCl) and 20% (w/w) feedstock load. Based on this ATPS, lipase was successfully purified to the PEG top phase and the purification fold of lipase was enhanced to 12.42, with a high yield of 93%. The partitioning and purification of lipase was also explored by using temperature-induced aqueous micellar two-phase system (AMTPS) composed of single nonionic surfactant. AMTPS offers a convenient and efficient method for the purification of lipase with large loading capacity and the potential of recycling surfactant for the preparation of new AMTPS. Based on the AMTPS which consisted of 24% (w/w) Pluronic L81 and 0.5% (w/w) potassium chloride, the selectivity of lipase has been enhanced to 0.035 and the lipase was purified 7.2 fold in the bottom phase. In the second step of purification, addition of potassium thiocyanate salt solution to the bottom micellar phase has resulted in back-extraction of the surfactant to top phase. The lipase was then recovered in new aqueous bottom phase with the yield of 89% and the partition coefficients of 0.34 and 4.50 for lipase and surfactant, respectively. Alcohol/salt ATPS was used to purify lipase. The high stability of Burkholderia sp. ST8 in the presence of organic solvents was exploited in alcohol/salt ATPS. Nine biphasic systems, comprised of alcohol-based top phase and salt-based bottom phase, were evaluated for their effectiveness in lipase purification. The optimum partition efficiency for the purification of lipase was obtained in an ATPS composed of 16% (w/w) 2-propanol and 16% (w/w) potassium phosphate in the presence of 4 % (w/w) NaCl. The purified lipase from the top phase had a purification fold of 13.5 and a yield of 99%. Furthermore, 2-propanol can be easily evaporated from the purified lipase and recycled for the subsequent batch of ATPS. Thereby, alcohol/salt ATPS is a viable operation for the cost-effective and rapid purification of lipase. Lastly, an extractive fermentation using ATPS was developed for the simultaneous cell cultivation and the downstream processing of extracellular lipase derived from Burkholderia sp. ST8. The cell growth and the lipase production in different types of ATPSs were investigated. An ATPS, which is composed of 9.6% (w/w) PEG 8000 and 1.0% (w/w) Dextran T500, provided the best condition for extractive lipase production. In this integrated process, biomass was accumulated in the bottom phase whereas the lipase was extracted to the top phase. High yield of lipase (92.1%) was recorded in the single batch operation. Repetitive batch of fermentation was progressively carried out by continuous replacement of the top phase every 24 h, which resulted in an average lipase concentration of 16.5 U/mL for seven extractive batch over the duration of 168 h. The extractive fermentation in ATPS is an attractive approach for the combination of the lipase production and the purification process, owing to the repeated use of the two-phase fermentation system and the ease of lipase recovery from fermentation culture.